Understanding and assessing personality across cultures: A scoping review - Hannah Sheppard; Boris Bizumic; Bruce Christensen; Conal Monaghan (PLoS ONE, 2026)
Previous reviews of personality trait instruments have questioned whether meaningful cross-cultural comparisons of personality can be made. Personality, however, extends beyond personality traits. The current scoping review utilized McAdams’s Three-Layer framework of personality to assess the cross-cultural validity of measures of traits, characteristic adaptations, and life narratives to deepen the understanding of whether personality can be effectively assessed across different cultures. 233 publications were identified from searching scientific databases, leading international journals in personality and assessment, and databases for specific personality instruments between the 23 rd of January and the 5 th of June 2024. The review identified models of personality that have been empirically or theoretically supported across different cultures, focusing on measures that are structurally equivalent across cultures and have strong validity estimates within non-Western cultures. This review principally focused on cross-cultural research published in English within the last 20 years (2004–2024), and concentrated on broad integrative models of personality, which investigate a myriad of personality constructs, such as personality traits, values, and beliefs. The majority of publications (59%) utilized personality trait models when assessing personality across-cultures. Although no instruments demonstrated evidence of full cross-cultural scalar invariance, the NEO-Personality Inventory Revised, and the International Personality Item Pool 120-item representation of the NEO-PI-R demonstrated the strongest evidence for validity and reliability in their cross-cultural personality trait assessment. The Schwartz values measure, the 21-item Portrait Values Questionnaire, also demonstrated acceptable psychometric properties and partial scalar measurement invariance across cultures. Some measures were found to perform well within specific cultures. Nonetheless, this review cautions against making inferences about differences in average levels of personality between cultures due to the lack of scalar invariance across nearly all personality measures.